The foundations of a new university reform from the Peruvian social movement Reinterpreting the quality, equity and relevance - Mendoza Vidal, Jorge Americo (2011)
In the last years, the University Reform Movement promoted by the Peruvian State has limitations. It lacks of a clear theoretical clarification of the categories proposed by the UNESCO: quality, fairness and relevance. Those categories have been applied inconsistently and used by private economic interests, when they should be oriented to public and national interests. Because of the Neoliberalism and Globalization, the Peruvian university social movement critiqued the political use of quality, fairness and relevance of the last governments. The Peruvian university movement learned from the twentieth century Reform and redefined its content from the scientific, democratic and national perspective. This is the basis for all quality standards that guarantees a scientific nature, equitable measures that ensure an identical education system for everyone under the same conditions, a politic education that focus on the development of national economic production. These are the foundations of the social movement in Peru.